A contribution to the empirics of food price behavior: the case of rice price dynamics in Italy - Barboza, Gustavo; Gavinelli, Laura; Pede, Valerien; Mazzucchelli, Alice; Di Gregorio, Angelo (Emerald Publishing Limited, 2020)
PurposeThe purpose is to detect the nonlinearity wholesale rice price formation process in Italy in the 1995–2017 period.Design/methodology/approachA nonlinear smooth transition autoregressive (STAR)-type dynamics model is used.FindingsWholesale rice prices are significantly affected by variations in the international price of rice as well as variations in Arborio price.Research limitations/implicationsThe limitations include policy recommendations for the production and commercialization of rice in Italy.Practical implicationsUnderstanding rice pricing dynamics and nonlinearity behavior is pivotal for the survival of the entire European and Italian rice supply chain.Originality/valueIn the extant literature, no evidence exists on non-linearity of rice prices in Italy.